2014
DOI: 10.1097/mpg.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

The Liver in Pediatric Gastrointestinal Disease

Abstract: Hepatic involvement is often encountered in gastrointestinal (GI) diseases, in part because of the close anatomic and physiologic relations between the liver and GI tract. Drainage of the mesenteric blood supply to the portal vein permits absorbed and/or translocated nutrients, toxins, bacterial elements, cytokines, and immunocytes to gain hepatic access. Liver problems in digestive disorders may range from nonspecific hepatocellular enzyme elevations to significant pathologic processes that may progress to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 208 publications
0
16
2
1
Order By: Relevance
“…A recent study carried out in the United Kingdom evaluating individuals with class III obesity in preoperative bariatric surgery [54] showed a 90% percentage of serum vitamin D deficiency, assessed in the form of 25(OH)D in the sample studied, data similar to our findings. Among the indicators of hepatocellular damage most widely used in the literature are GGT and AP transaminases [55], but in this study mean levels of ALT, AST, and AP among individuals with hepatic steatosis and steatohepatitis showed no significant differences. Although many studies have reported an increase in indicators of liver function and damage in individuals with various degrees of NAFLD [56, 57], these enzymes generally are normal in over 78% of individuals [58].…”
Section: Discussioncontrasting
confidence: 58%
“…A recent study carried out in the United Kingdom evaluating individuals with class III obesity in preoperative bariatric surgery [54] showed a 90% percentage of serum vitamin D deficiency, assessed in the form of 25(OH)D in the sample studied, data similar to our findings. Among the indicators of hepatocellular damage most widely used in the literature are GGT and AP transaminases [55], but in this study mean levels of ALT, AST, and AP among individuals with hepatic steatosis and steatohepatitis showed no significant differences. Although many studies have reported an increase in indicators of liver function and damage in individuals with various degrees of NAFLD [56, 57], these enzymes generally are normal in over 78% of individuals [58].…”
Section: Discussioncontrasting
confidence: 58%
“…Кроме того, была отмечена перекрестная чувствительность к антибактериальным препаратам группы бета-лактамов: гепатотоксичность последовательно возникала после применения эртапенема, цефтриаксона, препарата амоксициллин+клавулановая кислота, что соответствует данным H. D. Vo с соавт. [12].…”
Section: Discussionunclassified
“…Among the hepatocellular damage markers mostly used in the literature are the transaminases, GGT, and AP [ 22 ]. In this study, the ALT, AST, and AP mean levels among individuals with hepatic steatosis and steatohepatitis showed no significant differences.…”
Section: Discussionmentioning
confidence: 99%